A novel, easy and rapid method for constructing yeast two-hybrid vectors using In-Fusion technology. (25th May 2018) - Yu, Deshui; Liao, Libing; Zhang, Ju; Zhang, Yi; Xu, Kedong; Liu, Kun; Li, Xiaoli; Tan, Guangxuan; Chen, Ran; Wang, Yulu; Liu, Xia; Zhang, Xuan; et al.
Yeast two-hybrid systems are powerful tools for analyzing interactions between proteins. Vector construction is an essential step in yeast two-hybrid experiments, which require bait and prey plasmids. In this study, we modified the multiple cloning site sequence of the yeast plasmid pGADT7 by site-directed mutagenesis PCR to generate the pGADT7-In vector, which resulted in an easy and rapid method for constructing yeast two-hybrid vectors using the In-Fusion cloning technique. This method has three key advantages: only one pair of primers and one round of PCR are needed to generate bait and prey plasmids for each gene, it is restriction endonuclease- and ligase-independent, and it is fast and easily performed.